Principles and applications of Macroeconomics / Robert E. Hall, Marc Lieberman - Robert E. Hall (Thomson/South-Western, 2008)
PART I. PRELIMINARIES. 1. What Is Economics? 2. Scarcity, Choice, and Economic Systems. 3. Supply and Demand. PART II. MACROECONOMICS: BASIC CONCEPTS. 4. What Macroeconomics Tries to Explain. 5. Production, Income, and Employment. 6. The Monetary System, Prices, and Inflation. PART III. LONG-RUN MACROECONOMICS. 7. The Classical Long-Run Model. 8. Economic Growth and Rising Living Standards. PART IV. SHORT-RUN MACROECONOMICS. 9. Economic Fluctuations. 10. The Short-Run Macro Model. PART V. MONEY, PRICES, AND THE MACROECONOMY. 11. The Banking System and the Money Supply. 12. The Money Market and Monetary Policy. 13. Aggregate Demand and Aggregate Supply. PART VI. MACROECONOMIC POLICY. 14. Inflation and Monetary Policy. 15. Fiscal Policy: Taxes, Spending, and the Federal Budget. 16. Exchange Rates and Macroeconomic Policy